Allosteric Site Inhibitor Disrupting Auto-Processing of Malarial Cysteine Proteases. Issue 1 (December 2018) - Pant, A.; Kumar, R.; Wani, N.; Verma, S.; Sharma, R.; Pande, V.; Saxena, A.; Dixit, R.; Rai, R.; Pandey, K.
Abstract Falcipains are major haemoglobinases ofPlasmodium falciparum required for parasite growth and development. They consist of pro- and mature domains that interact via 'hot-spot' interactions and maintain the structural integrity of enzyme in zymogen state. Upon sensing the acidic environment, these interactions dissociate and active enzyme is released. For inhibiting falcipains, several active site inhibitors exist, however, compounds that target via allosteric mechanism remains uncharacterized. Therefore, we designed and synthesized six azapeptide compounds, among which, NA-01 & NA-03 arrested parasite growth by specifically blocking the auto-processing of falcipains. Inhibitors showed high affinity for enzymes in presence of the prodomain without affecting the secondary structure. Binding of NA-03 at the interface induced rigidity in the prodomain preventing structural reorganization. We further reported a histidine-dependent activation of falcipain. Collectively, for the first time we provide a framework for blocking the allosteric site of crucial haemoglobinases of the human malaria parasite. Targeting the allosteric site could provide high selectivity and less vulnerable to drug resistance.